Modern Lithuanian Stained Glass. - Bartenev, Igor; Ramanauskaité, Liudvika (Leningrad : Aurora Art Publishers, 1979)
Bružas, Bronius ; Dovydénas, Algirdas ; Garbauskas, Antanas ; Grušas, Bronius ; Juodenyté-Baginskiené, Ginta ; Kazimieraitis, Steponas ; Kulšys, Henrilas ; Mackélaite, Anorté ; Morkǔnas, Kazimieras ; Pocius, Liudvikas ; Šatǔnas, Konstantinas ; Stoškus, Algimantas ; Švarlys, Vutautas ; Ušinskaité, Filomena ; Ušinskas, Stasys
boek